Outdoor Learning Module For Senior High School Biological Learning Based On Understory Plants Research Findings At The Post-Bouxite Mining Lands, Singkep Island: Modul Outdoor Learning untuk Pembelajaran Biologi Sekolah Menengah Atas Berdasarkan Hasil Riset Keragaman Jenis Understory Plants pada Lahan Pascatambang Bauksit di Pulau Singkep - Sarah Ayugusetiana; Firdaus LN; Nursal Nursal (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2021)
This study aims to produce an outdoor learning for Senior High School Biological learning. New sources of knowledge for enriching the module were taken from research findings of understory plants grown on ex-bouxite mining lands in Singkep Island that were carried out on December 2019-February 2020. The ecological survey method with purposive sampling technique was used to inventory the diversity of understory plant species after revegetated in 2012, 2014 and 2015. The data of understory plant were identified using an identification guides. The Outdoor Learning module for Senior High School was designed by using the ADDIE model through three three stages, i.e. analyze, design, development. The quality of the Biology learning module’s based on Outdoor Learning is classified as good in terms of the level of validity, format, graphic, scientific illustrations, language as well as the feasibility of the module contents so that could be utilize by the Biology teacher’s for enriching the Biological teaching at Senior High School